INTERFERENCE ANALYSIS BETWEEN HAPS AND 5G CELLULAR SYSTEMSAT 2100 MHZ FREQUENCY - Ramdhani, Diky
In recent years, cellular telecommunications technology has entered the era of 5G (Fifth Generation) cellular technology. In Indonesia, the provision of 5G cellular services has many challenges with the vast territory of Indonesia which is made up of many islands. One solution to this problem is HAPS (High Altitude Platform Station). In this thesis, interference analysis will be carried out on the 5G cellular system and HAPS system at2100 MHz frequency band, which is one of the HAPS frequency bands used for 5G cellular systems in Indonesia. The interference analysis is carried out by modeling a 5G cellular system whose service area is adjacent to the HAPS system. The interfered cellular mobile station is located at the edge of the cellular cell adjacent to the HAPS cell. The interference on this cellular mobile station originates from the cellular base station and HAPS base station. The channel models used are Urban Macro, Urban Micro, and Rural Macro to represent the environment in a 5G cellular system. With this modeling, the C/I value of the inferred mobile station is calculated. This thesis analyzes the effect of the number of HAPS users and the distance to the HAPS nadir on the C/I value of the inferred mobile station. The results show that these two parameters have a significant impact on the value of C/I. Apart from that, the thesis also carried out an analysis of the effect of HAPS movements on C/I values. The results show that HAPS movement both vertically and horizontally has no significant effect on the C/I value of cellular mobile stations.